Toward the next generation of vascularized human neural organoids. Issue 1 (22nd August 2022) - Li, Minghui; Gao, Lixiong; Zhao, Ling; Zou, Ting; Xu, Haiwei
Abstract: Thanks to progress in the development of three‐dimensional (3D) culture technologies, human central nervous system (CNS) development and diseases have been gradually deciphered by using organoids derived from human embryonic stem cells (hESCs) or human induced pluripotent stem cells (hiPSCs). Selforganized neural organoids (NOs) have been used to mimic morphogenesis and functions of specific organs in vitro. Many NOs have been reproduced in vitro, such as those mimicking the human brain, retina, and spinal cord. However, NOs fail to capitulate to the maturation and complexity of in vivo neural tissues. The persistent issues with current NO cultivation protocols are inadequate oxygen supply and nutrient diffusion due to the absence of vascular networks. In vivo, the developing CNS is interpenetrated by vasculature that not only supplies oxygen and nutrients but also provides a structural template for neuronal growth. To address these deficiencies, recent studies have begun to couple NO culture with bioengineering techniques and methodologies, including genetic engineering, coculture, multidifferentiation, microfluidics and 3D bioprinting, and transplantation, which might promote NO maturation and create more functional NOs. These cutting‐edge methods could generate an ever more reliable NO model in vitro for deciphering the codes of human CNS development, disease progression, and translational application. In this review, we will summarize recent technological advances in culture strategies to generate vascularized NOs (vNOs), with a special focus on cerebral‐ and retinal‐organoid models.